2004
DOI: 10.1002/ejic.200400460
|View full text |Cite
|
Sign up to set email alerts
|

Binucleating Aza‐Sulfonate and Aza‐Sulfinate Macrocycles — Synthesis and Coordination Chemistry

Abstract: The preparation and ligating properties of S-oxygenated derivatives of a macrobinucleating hexaazadithiophenolate macrocycle H 2 L 1 of the Robson type towards nickel(II) and zinc(II) ions are reported. Nickel complexes of the hexaazadi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 66 publications
2
25
0
Order By: Relevance
“…The shift to higher field can be explained by the ring current effect. The coligands are located above the center of the two aryl rings of (L 2 ) 2À in the shielding region [57]. This results in the observed chemical shift change to higher field.…”
Section: The Ligand Matrix As a Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…The shift to higher field can be explained by the ring current effect. The coligands are located above the center of the two aryl rings of (L 2 ) 2À in the shielding region [57]. This results in the observed chemical shift change to higher field.…”
Section: The Ligand Matrix As a Mediummentioning
confidence: 99%
“…This is mainly due to two factors: (i) the decrease in the ligand field strength and (ii) the increase in the steric requirements upon going from a secondary to a tertiary amine donor function [55]. In order to examine whether the properties of our complexes are affected by the N-alkyl substituents, we have characterized analogous complexes of the two macrocycles H 2 L 1 and H 2 L 2 by various spectroscopic methods (IR, UV/Vis, EPR, 57 Fe-M€ ossbauer spectroscopy), cyclic voltammetry, temperature-dependent magnetic susceptibility measurements and X-ray crystallography. The most important findings of these investigations are as follows:…”
Section: Effects Of N-alkylation On the Molecular And Electronic Strumentioning
confidence: 99%
“…[9][10][11] In previous work, we always used the perchlorate salts in such oxidation reactions. [7] We now found that this method works for the tetraphenylborate salts as well. …”
Section: Syntheses Of Metal Complexesmentioning
confidence: 95%
“…Analogous pairs of dinuclear [Ni 2 (L1)(LЈ)] + and [Ni 2 (L2)(LЈ)] + complexes have been reported with LЈ = Cl -, CH 3 CO 2 -, PhCO 2 -, 3-Cl-C 6 H 4 CO 2 -. [7,8] It was found that the structures and chemical properties are strikingly different, a fact attributable to the conversion of the cases converted to μ 1,3 -bridging sulfonate groups to generate N 3 Ni(μ 1,3 -SO 3 R) 2 Upon oxidation the magnetic properties are affected. In contrast to 1-3, which exhibit an intramolecular ferromagnetic exchange interaction (S = 2 ground state), the spins of the nickel(II) (S i = 1) ions in 4-6 are antiferromagnetically coupled, the coupling constants J being -1.39 cm -1 (4), -1.43 cm -1 (5), and -1.60 cm -1 (6) (H = -2JS 1 S 2 ) to yield a diamagnetic S = 0 ground state.…”
Section: Invariably Forms Mixed-ligand [M 2 (L1)(lј)]mentioning
confidence: 98%
See 1 more Smart Citation